Sonny’s Blues: Art, Suffering, Racism, and Redemption through Music in James Baldwin’s Harlem - Adhikari, Bhoj Raj (PT. Riset Press International, 2025)
This paper critically analyzes James Baldwin’s short story Sonny’s Blues as a socio-cultural narrative of suffering, racial segregation, and the redemptive power of music. Set in Harlem, the story explores how African American identity, familial relationships, and artistic expression intersect in the lives of two brothers. Through the lens of blues and bebop jazz, the research interrogates how Baldwin constructs a symbolic framework of trauma, communication, and salvation. The study highlights the story's religious imagery, racial critique, and musical metaphors to understand Baldwin’s broader commentary on black suffering and resistance.